2016
DOI: 10.1108/ecam-01-2016-0009
|View full text |Cite
|
Sign up to set email alerts
|

Developing a tailored RBS linking to BIM for risk management of bridge projects

Abstract: Purpose-The purpose of this paper is to address the current theoretical gap in integrating knowledge and experience into BIM for risk management of bridge projects by developing a tailored Risk Breakdown Structure (RBS) and formalising an active link between the resulting RBS and Building Information Model (BIM). Design/methodology/approach-A three-step approach is used in this study to develop a tailored RBS for bridge projects and a conceptual model for the linkage between the RBS and BIM. Firstly, the integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(18 citation statements)
references
References 45 publications
0
17
0
1
Order By: Relevance
“…Marzouk and Hisham [18] presented the application of BIM for the cost and time management of bridge infrastructure, with a five-dimensional approach (3D plus time and cost) using the BIM software. Zou et al [19] demonstrated the benefits of using BIM in the risk management of bridge projects. They emphasised that 3D visualisation and 4D construction scheduling facilitate risk identification, risk analysis and communication between different parties at an early stage.…”
Section: Bim Adoption For Bridge Projectsmentioning
confidence: 99%
“…Marzouk and Hisham [18] presented the application of BIM for the cost and time management of bridge infrastructure, with a five-dimensional approach (3D plus time and cost) using the BIM software. Zou et al [19] demonstrated the benefits of using BIM in the risk management of bridge projects. They emphasised that 3D visualisation and 4D construction scheduling facilitate risk identification, risk analysis and communication between different parties at an early stage.…”
Section: Bim Adoption For Bridge Projectsmentioning
confidence: 99%
“…Wang et al [18] summarized the advantages of the application of BIM technology in bridge health monitoring and built a practical framework for engineering applications based on examples. Zou et al [19] applied BIM technology to bridge risk management to realize bridge risk identification and analysis. Davila Delgado J M et al [20] modeled the structural performance monitoring system in the BIM environment so that the sensor data can be visualized on the BIM model directly.…”
Section: The Concept Of Building Information Modeling (Bim) Was Firstmentioning
confidence: 99%
“…Zou et al (2016a) took a three-step BIM-based approach toward risk management in the paper about BIM and BIM-related technologies. BIM's integration with knowledge-based systems is one of the cases discussed in this paper in which applying integrated knowledge management and BIM, a novel method of identifying the root causes of failure has been proposed.…”
Section: Background and Related Researchmentioning
confidence: 99%